Candidaemia or candidasis: controversy of staphylococcus sexually transmitted infection? (2016)
Herbal medications are becoming increasingly popular but a most-extraordinary claim by traditional/herbal medical practitioners relates to a Gram-positive bacterium, Staphylococcus, which has been depicted as a deadly sexually transmitted disease that manifest in the form of worms and other symptoms; with contributory roles including infertility, sexual dysfunction and impotency. They further boasted that they are the only ones that possessed the remedy (herbal) for the Staphylococcus sexually transmitted scourge. In the absence of distinguishing phenotypic taxonomic tools, Staphylococcus and Candida spp. may be confused for each other. However, Staphylococcus is a bacterium and not an infection; therefore, there must be more to the traditional medical practitioners’ boasts in ability to cure an infection that was not an infection in the first place. In conclusion, the common sense is that candiaemia or candidiasis is most likely the misdiagnosed sexually transmitted Staphylococcus disease, which is of significant human clinical health issue.